2004 IEEE International Reliability Physics Symposium. Proceedings
DOI: 10.1109/relphy.2004.1315418
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thermal gradients on the electromigration life-time in power electronics

Abstract: microstructure containing lots of triple points, and harsh operating conditions may make power IC's more vulnemble than standard devices. In this paper we present strongly reduced EM-lifetimes upon ABSTRACTThe combined effects of electromigration and thennomigration are studied. Significantly shorter electromigration lifetimes are observed in the presence of a temperature gradient. This cannot be explained hy thennomigation only, but is attxibuted to the effect of temperature grament on electromigration-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 7 publications
(5 reference statements)
1
21
0
Order By: Relevance
“…A significant drop in the median time to failure occurs if the temperature gradient is in the opposite direction. Nguyen et al [23] performed similar experiments with built-in heating element in the EM test structure. From their experiments, they found that the time to failure with temperature gradients of 0.09, 0.19 and 0.28 K/Am were reduced to 90%, 40% and 9% of the time to failure without temperature gradient, respectively.…”
Section: Experimental Evidencesmentioning
confidence: 99%
“…A significant drop in the median time to failure occurs if the temperature gradient is in the opposite direction. Nguyen et al [23] performed similar experiments with built-in heating element in the EM test structure. From their experiments, they found that the time to failure with temperature gradients of 0.09, 0.19 and 0.28 K/Am were reduced to 90%, 40% and 9% of the time to failure without temperature gradient, respectively.…”
Section: Experimental Evidencesmentioning
confidence: 99%
“…(21) and (22)] allows us to assess the importance of the lognormal standard deviation (or shape factor d ) of the grain size distribution on the probability of early failure P cf in near-bamboo as-patterned aluminum lines. It is clear from Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Guo et al [22] reported that EM in aluminum interconnect is strongly affected by the relative direction of electron wind and thermal gradients, while Nguyen et al [23] found that temperature gradients greatly enhance EM in aluminum interconnect. Following the stress build-up model introduced in Section II, the atomic flux due to EM can be modeled by , and the stress build-up at a specific location is caused by the divergence of atomic flux at that location, i.e.,…”
Section: A Em Model With Spatial Thermal Gradientsmentioning
confidence: 99%
“…When compared with (4), (11) introduces a third term , which captures the atomic flux divergence induced by spatial thermal gradients along the interconnect. Although temperature gradient itself will cause migrations of atoms from high temperature to low temperature, a phenomenon called thermomigration (TM), the atomic flux due to TM is generally believed to be much smaller than that due to EM [23]. Therefore, TM is not explicitly modeled in (11).…”
Section: A Em Model With Spatial Thermal Gradientsmentioning
confidence: 99%